2009
DOI: 10.1162/rest.91.3.558
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Volatility

Abstract: This paper examines the mechanisms through which output volatility is related to trade openness using an industry-level panel data set of manufacturing production and trade. The main results are threefold. First, sectors more open to international trade are more volatile. Second, trade is accompanied by increased specialization. These two forces imply increased aggregate volatility. Third, sectors that are more open to trade are less correlated with the rest of the economy, an effect that acts to reduce overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(220 citation statements)
references
References 47 publications
(64 reference statements)
9
210
0
1
Order By: Relevance
“…Imperfect knowledge of local conditions may also leave exporters more vulnerable to cost or demand shocks in foreign markets. A number of studies suggest that exports are more volatile than domestic sales (Vannoorenberghe, 2012) and that openness to trade -at least in some cases -raises the volatility of output at the level of sectors (di Giovanni and Levchenko, 2009) or countries (Rodrik, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imperfect knowledge of local conditions may also leave exporters more vulnerable to cost or demand shocks in foreign markets. A number of studies suggest that exports are more volatile than domestic sales (Vannoorenberghe, 2012) and that openness to trade -at least in some cases -raises the volatility of output at the level of sectors (di Giovanni and Levchenko, 2009) or countries (Rodrik, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Rodrik, 1998;Easterly et al, 2001;Bejan, 2006;di Giovanni and Levchenko, 2009). Caselli et al (2014) show that, at the macroeconomic level, the diversification of sales across countries made possible by international trade can act as a source of stability.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between trade openness and overall volatility is found to be positive (Giovanni and Levchenko, 2009); political instability tends to increase volatility (Dutt and Mitra, 2008); geography and institutions also play a role, as remote countries are more likely to experience greater volatility in output growth (Malik and Temple, 2009). Finally, Fountas and Karanasos (2007) find mixed evidence regarding the relationship between inflation and volatility of the output growth.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In fact, the fluctuations of the output growth crucially determine a large number of economic outcomes (Giovanni and Levchenko, 2009) and therefore also the perceived success or failure of economic policies. Higher output volatility is shown to be connected to lower private investment (Aizenman and Marion, 1999), substantial welfare effects (Barlevy, 2004), and eventually also to lower long-run economic growth (e.g., Ramey and Ramey, 1995;Imbs, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Imbs (2004) and Giovanni and Levchenko (2009) showed that there is a strong tie between specialization and economic volatility. Beine and Coulombe (2007), Ortiz (2012), and Elhiraika, Abuouhakar, and Muhammad (2014) found that diversification should be promoted for growth.…”
Section: Existing Studiesmentioning
confidence: 99%